Pengaruh Likuiditas, Ukuran Perusahaan, dan Konservatisme Akuntansi terhadap Kualitas Laba - Rassya Islamay Arivia; Syaiful Syaiful (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study aims to evaluate the effect of liquidity, firm size, and accounting conservatism on earnings quality. Using a population of manufacturing companies listed in 2021-2022, the research sample was taken through purposive sampling technique, resulting in 56 companies that met the criteria. Data analysis was carried out using multiple linear regression techniques using SPSS. The results showed that the variables of liquidity and accounting conservatism had no significant effect on earnings quality, while company size had a significant positive effect on earnings quality. These findings indicate that firm size plays an important role in determining earnings quality, while liquidity and accounting conservatism factors may not have a direct impact in the context of the manufacturing companies studied.